2001
DOI: 10.1002/ldr.447
|View full text |Cite
|
Sign up to set email alerts
|

Soil rehabilitation through afforestation: evaluation of the performance of Eucalyptus and pine plantations in a Nigerian Savanna environment

Abstract: On the outskirts of Zaria, northern Nigeria, Eucalyptus camaldulensis and Pinus oocarpa plantations have been established to satisfy both land rehabilitation and agroindustrial objectives. Soils of the plantations and adjacent unafforested degraded sites where major in¯uences from soil type and management were minimal were sampled to provide data for a parallel investigation of the effect of afforestation on soil rehabilitation. Three adjacent age±grade plantations in respect of each tree species were involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
1
9
0
3
Order By: Relevance
“…The higher clay at 0-15 cm soil depth on CBCVTS might be due to intensive and continuous cultivation which may reduces downward movement of clay particles within the soil profile. This finding is in agreement with findings of Jaiyeoba [28]. The higher sand fraction on CBCTS was due to selective removal of clay fraction by erosion [29][30][31][32][33][34].…”
Section: Soil Physical Propertiessupporting
confidence: 91%
“…The higher clay at 0-15 cm soil depth on CBCVTS might be due to intensive and continuous cultivation which may reduces downward movement of clay particles within the soil profile. This finding is in agreement with findings of Jaiyeoba [28]. The higher sand fraction on CBCTS was due to selective removal of clay fraction by erosion [29][30][31][32][33][34].…”
Section: Soil Physical Propertiessupporting
confidence: 91%
“…While most studies support the idea that trees enhance K s (Table 1), the results of some suggest that this is not universally true. For example, Jaiyeoba (2001), investigating the effect of reforestation on degraded land in Nigeria, found that a significant increase in K s was observed under only one of the six plantations studied. Yeates and Boag (1995) reported higher soil permeability in pasture compared with the Pinus radiata agro-forestry systems in their study.…”
Section: Introductionmentioning
confidence: 95%
“…For example, during the investigation of stands, we found that some karst regions with higher grades (moderate RD (MRD) or intensive RD (IRD)) had been enclosed for afforestation. This measure is beneficial to rehabilitation and sustainable management of karst lands (Jaiyeoba, 2001).…”
Section: Introductionmentioning
confidence: 99%